2014
DOI: 10.1111/gcb.12543
|View full text |Cite
|
Sign up to set email alerts
|

Net uptake of atmospheric CO 2 by coastal submerged aquatic vegetation

Abstract: ‘Blue Carbon’, which is carbon captured by marine living organisms, has recently been highlighted as a new option for climate change mitigation initiatives. In particular, coastal ecosystems have been recognized as significant carbon stocks because of their high burial rates and long-term sequestration of carbon. However, the direct contribution of Blue Carbon to the uptake of atmospheric CO2 through air-sea gas exchange remains unclear. We performed in situ measurements of carbon flows, including air-sea CO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 59 publications
6
85
0
1
Order By: Relevance
“…The f CO 2 variations in the lagoon, which are among the parameters that regulate air-water CO 2 fluxes, have been confirmed to be related to mixing of lagoon water with freshwater coming from rivers and with biological processes such as photosynthesis (Tokoro et al, 2014). Given that the former and latter phenomena are caused by the semi-diurnal tidal cycle and diel changes of irradiance, respectively, the peaks in the power spectrum are consistent with the results of Tokoro et al (2014). This consistency is a good demonstration of the utility of the PP2.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The f CO 2 variations in the lagoon, which are among the parameters that regulate air-water CO 2 fluxes, have been confirmed to be related to mixing of lagoon water with freshwater coming from rivers and with biological processes such as photosynthesis (Tokoro et al, 2014). Given that the former and latter phenomena are caused by the semi-diurnal tidal cycle and diel changes of irradiance, respectively, the peaks in the power spectrum are consistent with the results of Tokoro et al (2014). This consistency is a good demonstration of the utility of the PP2.…”
Section: Discussionmentioning
confidence: 94%
“…Freshwater flows into the western basin through several rivers that run through the surrounding grass farms, and seawater is exchanged through the lagoon mouth, which opens to the Okhotsk Sea. A previous study has found that the air-water CO 2 flux in the lagoon is affected by changes of salinity caused by the inflow of river water and tides as well as by changes of dissolved inorganic carbon resulting from biological processes such as photosynthesis (Tokoro et al, 2014). The measurement platform was built at the same site used in that previous study (43 • 19.775 ′ N, 145 • 15.463 ′ E); the effects of photosynthesis and changes in salinity are most notable at this location in the lagoon (Tokoro et al, 2014).…”
Section: Field Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The net ecosystem production of seagrass meadows is a key factor determining whether they are sinks or sources of C air (Maher and Eyre, 2012;Tokoro et al, 2014;Watanabe and Kuwae, 2015). Previously, however, such an exchange of CO 2 has been thought to occur only via the air-water interface with subsequent exchange with seagrasses as DIC.…”
Section: Resultsmentioning
confidence: 99%
“…Lake Furen is approximately 1-m deep, with the exception of water routes that cause it to deepen towards the main channel (maximum depth: 11 m). Seagrasses (Zostera marina L.) fill approximately 67% of the lake area, and their aboveground biomass ranges seasonally between 16 and 318 g dry weight m −2 (Tokoro et al 2014). The lake freezes from December to March.…”
Section: Field Samplingmentioning
confidence: 99%